The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.34172/jhp.2022.46
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the chemical compositions of six essential oils and evaluation of their antioxidant and antibacterial activities against some drug-resistant bacteria in aquaculture

Abstract: Introduction: The extensive use of chemicals and antimicrobial agents in aquaculture has decreased the immune mechanisms of cultivated species and promoted the emergence of drug-resistant microorganisms leading to diseases among cultivated fish, affecting consumers’ health. Thus, the investigation of natural antibacterial and anti-stress agents is crucial. In the current study, we focused on the evaluation of the potential use of essential oils (EOs) as an antioxidant and antimicrobial agents in aquaculture. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition, it is interesting to note that a previous study mentioned that there are many antioxidants, especially various safe plants that have antioxidant activity. They found that essential oils (EO) extracted from six chemical components acted as antioxidants and protected fish from oxidative stress ( 49 ). This implies that agents with antioxidant activity might be effective against ASCVD related to oxidative stress, and antioxidant drugs might be a new strategy for the prevention of ASCVD, and the relationship between the two and the mechanism of action still needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is interesting to note that a previous study mentioned that there are many antioxidants, especially various safe plants that have antioxidant activity. They found that essential oils (EO) extracted from six chemical components acted as antioxidants and protected fish from oxidative stress ( 49 ). This implies that agents with antioxidant activity might be effective against ASCVD related to oxidative stress, and antioxidant drugs might be a new strategy for the prevention of ASCVD, and the relationship between the two and the mechanism of action still needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Morocco: 23.8% ( 5) [Baghouz, 2022;Chbel, 2022;El-Kharraf et al, 2022;Elyemni, 2019;Gourich, 2022] Dried: 81.0% (17) [Alvarado, 2023;Arfa, 2022;Baghouz, 2022;Casas, 2023;Chbel, 2022;El-Kharraf et al, 2022;Elyemni, 2019;Farhat, 2017;Frescura, 2019;Ganjali, 2017;Gezici, 2017;Gourich, 2022;Karalija, 2020;Luca, 2023;Wollinger, 2016;Yeddes, 2022] Leaves: 75.0% (15) [Alvarado, 2023;Arfa, 2022;Baghouz, 2022;Casas, 2023;Chbel, 2022;El-Kharraf, 2022;Farhat, 2017;Frescura, 2019;Gezici, 2017;Gourich, 2022;Luca, 2023;Mekonnen, 2016;Sadeh, 2019;Wollinger, 2016;Yeddes, 2022] Tunisia: 14.2%…”
Section: Rosmarinus Officinalisunclassified